2018
DOI: 10.1159/000490221
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Eryptosis by Afatinib

Abstract: Background/Aims: The epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor afatinib is primarily utilized for the treatment of non-small cell lung carcinoma. The drug is at least partially effective by triggering suicidal tumor cell death. Side effects of afatinib treatment include anemia. At least in theory, afatinib induced anemia could be secondary to stimulation of suicidal erythrocyte death or eryptosis, characterized by cell shrinkage and cell membrane scrambling with phosphatidylserine trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 140 publications
0
4
0
Order By: Relevance
“…Experiments were then performed to determine the upstream regulatory factors for Sirt3 upregulation in response to liraglutide treatment. Previous studies have identified the ERK-Yap axis as a novel signaling pathway that modifies mitochondrial function (36)(37)(38). Therefore, the present study investigated whether the ERK-Yap signaling pathway was involved in liraglutide-mediated Sirt3 activation.…”
Section: Liraglutide Protects Mitochondrial Function By Upregulating Sirt3 Expressionmentioning
confidence: 92%
“…Experiments were then performed to determine the upstream regulatory factors for Sirt3 upregulation in response to liraglutide treatment. Previous studies have identified the ERK-Yap axis as a novel signaling pathway that modifies mitochondrial function (36)(37)(38). Therefore, the present study investigated whether the ERK-Yap signaling pathway was involved in liraglutide-mediated Sirt3 activation.…”
Section: Liraglutide Protects Mitochondrial Function By Upregulating Sirt3 Expressionmentioning
confidence: 92%
“…The characteristics of eryptosis involves dysfunctional ion exchange, cell shrinkage, ceramide accumulation, cell membrane vesiculation due to cytosolic calcium overload, and membrane phospholipid scrambling with alteration of the cell membrane asymmetry and phosphatidylserine (PS) exposure at the cell surface [ 9 , 10 ]. Ca 2+ influx opens Ca 2+ -sensitive K + channels, or Gardos channels, leading to subsequent loss of KCl, hyperpolarization of the membrane, loss of water, and cell shrinkage [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The process of eryptosis regulation is complex, implicating a multitude of cellular machinery, and there are various triggers and inhibitors. Several kinases, including cyclin-dependent kinase 4, p38 mitogen-activated kinase, casein kinase 1α (CK1α), mitogen- and stress-activated kinase MSK1/2, and Janus-activated kinase JAK3, have been shown to participate in the stimulation or inhibition of eryptosis [ 10 , 19 ]. Many food-derived phytochemicals and natural compounds, including phenolic compounds and alkaloids, with antioxidant and anti-inflammatory properties have been reported to prevent eryptosis-driven cell death and associated clinical conditions [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ample evidence has identified Mst1 as an activator of caspases to initiate the apoptotic signaling pathway 4. The anticancer effects of Mst1 have also been reported in several tumors such as colorectal cancer, prostate cancer, lung cancer and liver cancer 5. Notably, previous studies have found that Mst1 is increased in HER2-positive and triple-negative breast cancer patients treated with neoadjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%